Pengaruh Dimensi Ekuitas Merek Terhadap Keputusan Pembelian Produk Pencuci Mulut (Mouthwash) - Dudi Permana; Christina Catur Widayati; Lina Winny (Jurnal Manajemen, 2018)
The purpose of this study is to determine the partial effect of brand awareness, brand association, perceived quality and brand loyalty on purchase decision in Betadine mouthwash. Two hundred samples are collected from the user and prospective user in Jakarta. the analytichal method used is descriptive and multiple linear regression. The result are (a) the partial effect of brand awareness, brand associaton, brand loyalty are positive and significant to purchase decision but not significant by perceived quality. (b) the highest correlation is achieved by brand awareness. Brand awareness was successfull formed by brand recognation as foundation but then it was stagnant on brand recall even less on top of mind. (c) purchase decision indicators has showed that consumer position is not ready in purchase decision and even less in re-purchase.